2011
DOI: 10.1002/bio.1207
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for sensing of methimazole using gold nanoparticle‐catalyzed chemiluminescent reaction

Abstract: Based on the inhibition effect of methimazole (MMI) on the reaction of luminol-H(2)O(2) catalyzed by gold nanoparticles, a novel chemiluminescence (CL) method was developed for the determination of MMI. Under the optimum conditions, the relative CL intensity was linearly related to MMI concentration in the range from 5.0 × 10(-8) to 5.0 × 10(-5) mol L(-1). The detection limit was 1.6 × 10(-8) mol L(-1) (S/N=3), and the RSD for 6.0 × 10(-6) mol L(-1) MMI was 4.83 (n=11). This method has high sensitivity, wide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Chemiluminescence (CL), light emission induced by chemical reactions, has been intensively investigated for many years. Due to its many advantages such as high sensitivity, low detection limit and wide linear dynamic ranges that can generally be achieved with simpler instruments, CL and related analytical techniques have been developed as important and powerful tools in different fields (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Chemiluminescence (CL), light emission induced by chemical reactions, has been intensively investigated for many years. Due to its many advantages such as high sensitivity, low detection limit and wide linear dynamic ranges that can generally be achieved with simpler instruments, CL and related analytical techniques have been developed as important and powerful tools in different fields (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…E-mail: fahimehjalali@yahoo.com. chromatography (Blanchflower et al, 1997;Kusmierek and Bald, 2007), gas chromatography-mass spectrometry (Zhang et al, 2005), flow-injection analysis with chemiluminescence detection (Economou et al, 2004), spectrophotometry (Jovanovic et al, 1992), fluorescence probe method (Dong et al, 2009) and gold nanoparticlecatalyzed chemiluminescence reaction (Sheng et al, 2011). Electrochemical methods, due to their advantages such as high sensitivity, high speed, and low-cost have been used in pharmaceutical analysis for a long time.…”
Section: Methimazole Mmzmentioning
confidence: 99%
“…Nanoparticles (NPs) have recently attracted strong research attention because of their unique physical and chemical properties. Moreover, NPs are used as nanocatalysts to enhance a variety of CL reactions [21][22][23][24][25][26]. With the development of nanotechnology, researchers demonstrated that the NPs-catalyzed CL system offered potential applications in analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%